2019
DOI: 10.1080/21645515.2019.1661754
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of vaccination uptake, and influenza vaccine effectiveness in preventing deaths and hospital admissions in the elderly population; Treviso, Italy, 2014/2015-2016/2017 seasons

Abstract: Seasonal influenza is an important cause of morbidity and mortality, particularly among the elderly population. Determinants of vaccination uptake and its impact on health outcomes in the seasons 2014/ 2015-2016/2017 in elderly living in Treviso area (Veneto Region, NorthEastern Italy) were evaluated. A retrospective cohort study was conducted combining information from several health administrative databases, and multiple Poisson regression models were applied to evaluate the influenza vaccine effectiveness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…In particular, Voordouw et al showed that annual influenza vaccination and revaccination were associated with a reduction in all-cause mortality risk, similarly in healthy and comorbid subjects of 80 years and older (hazard ratio 0.81, 95% interval confidence: 0.66–1.00; and 0.69, 0.61–0.78, respectively) [ 23 ]. In accordance with our results, a recent study in an elderly Italian population highlighted that influenza vaccine was equally effective for death prevention in all age groups (≤74, 75–84 and ≥85 years old) [ 24 ]. Other authors, in a large cohort study of subjects over 65 years of age, noted a decrease in mortality of 14%, 19% and 1% associated with vaccination during three consecutive winter seasons between 1998 and 2001 [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…In particular, Voordouw et al showed that annual influenza vaccination and revaccination were associated with a reduction in all-cause mortality risk, similarly in healthy and comorbid subjects of 80 years and older (hazard ratio 0.81, 95% interval confidence: 0.66–1.00; and 0.69, 0.61–0.78, respectively) [ 23 ]. In accordance with our results, a recent study in an elderly Italian population highlighted that influenza vaccine was equally effective for death prevention in all age groups (≤74, 75–84 and ≥85 years old) [ 24 ]. Other authors, in a large cohort study of subjects over 65 years of age, noted a decrease in mortality of 14%, 19% and 1% associated with vaccination during three consecutive winter seasons between 1998 and 2001 [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…Eight studies reported data on only one season 22,26–29,31,33,37 ; Rizzo et al reported data from 1970 to 2001, 34,35 and Bertolani et al reported data from 2008 to 2015 24 . The other studies reported data on a period of up to four seasons 23,24,30,32,36 . The characteristics of included studies are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The third is that the pneumococcal vaccination rate among adults 65 and over has been described as “extremely low in Italy” [ 168 ]. In contrast to Germany, Iceland, Israel, South Korea, Australia, and the U. S., where the over 64 adult pneumococcal vaccination rate is above 50% ( Table 1 ), in the Liguria region of Italy, it was between 26 and 31% [ 168 ]; 24.9% in Calabria (“among the highest in Italy”) [ 170 ]; 20% in the Friuli Venezia Giulia region [ 171 ]; 15.4% in Veneto [ 172 ]; and averaged only 5% per year in each of ten years in the Italian region of Puglia, reaching a cumulative total of no more than 24–30% [ 173 ]. In consequence, even as infant rates of IPD have been falling in recent years, rates among adults over 64 have been increasing and now account for more than two-thirds of all cases in Italy [ 87 , 88 , 151 ].…”
Section: Discussionmentioning
confidence: 99%